Fatores determinantes à importação de produtos siderúrgicos - Brito, Claudio Lustosa da Costa (2011)
The recent growing on importation on Brazil, especially on steel products, is follow by a discussion over the competitiveness of products, companies, markets and countries. The Ceará State reflects this occurrence of importing steel products, thus approximately 15% of all steel imported from Brazil enter through Ceará’s ports. Therefore, the proposal of this study is to identify the determinant factors of importing steel products by the metallurgical companies on Ceará State. Based on the theoretical landmark it was analyzed the steel market and the decision of metallurgical companies to import, as way of answering the question: what are the factors determining the import steel products? The research characterizes as quantitative and exploratory, under a descriptive structure, with procedures of documentary research, ex post facto, using secondary and primary sources. An enquiry survey was applied to 13 executives of importing metallurgical companies, identifying the competitive factors. After the analyses of the survey, interviews were applied in the office of former answering executives trying to clarify some points not concluded through the survey. It was observed the tendency of purchasing decision based mostly on the price, reinforcing o character of commodities of the steel products imported.